The Command of Gratitude in the Qur'an - Salman Muzaki; Adnan Adnan (UIN Sunan Gunung Djati Bandung, 2021)
This study discusses gratitude, because gratitude is a very important teaching in Islam, so that in the Qur'an it is called remembrance and worship of Allah. The method used in this research is qualitative through literature study with content analysis. The research discussion includes general views on gratitude, the meaning of gratitude in the Qur'an, and the concept of gratitude in the Qur'an. This study concludes that Gratitude is an acknowledgment that we do to Allah as the giver of favors, with gratitude Allah will always add to the enjoyment he has given and gratitude is one of the highest levels to Allah.